Pengembangan Aplikasi eRaport Perkembangan Latihan Anak Didik Sekolah Sepakbola Berbasis Web - Hudaya, Barda (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This article discusses the development of a web-based application for report cards or progress reports of soccer school students using Codeigniter 4. The purpose of this research is to design and implement an application that can facilitate the management and evaluation of soccer school students' performance. The method used in this research is prototyping, which involves several stages such as planning, analysis, design, implementation, testing, and evaluation. The results show that the application can perform various functions such as data input, data processing, data output, and data storage. The application can also generate report cards or progress reports for each student based on their skills and achievements. The conclusion of this research is that the web-based application using Codeigniter 4 can be a useful tool for soccer school management and education